Oral Ibuprofen versus Intravenous Indomethacin for Closure of Patent Ductus Arteriosus in Very Low Birth Weight Infants - Cheng Han Lee; Hsiao-Neng Chen; Long-Yen Tsao; Chien-Chou Hsiao; Meng-Luen Lee (Pediatrics and Neonatology)
The purpose of this study is to compare the effects and complications of pharmacologic closure of patent ductus arteriosus (PDA) by intravenous indomethacin or oral ibuprofen in neonates weighing <1500 g at birth [very low birth weight (VLBW) infants]. Methods: This is a retrospective study of infants treated with intravenous indomethacin (0.2 mg/kg initially followed by two doses at 24-hour intervals) or oral ibuprofen (10 mg/kg initially followed an interval of 24 hours by two doses of 5 mg/kg) for symptomatic PDA in a neonatal intensive care unit at a medical center in Taiwan during the period of January 2005 to December 2010. Results: A total of 88 infants received indomethacin and 52 received oral ibuprofen. Among the survivors, the closure rate without surgical ductal ligation was 70.5% (62/88) in the indomethacin group and 61.5% (32/52) in the ibuprofen group (p = 0.342). The incidence rates of oliguria and elevated serum creatinine were significantly lower in the ibuprofen group (p =0.002 and p =0.022, respectively). There was no significant difference in incidence of upper gastrointestinal hemorrhage or necrotizing enterocolitis between the ibuprofen and indomethacin groups (17.3% versus 23.9%; 3.8% versus 11.3%). Conclusion: In infants with VLBW, oral ibuprofen is as effective as intravenous indomethacin for closure of PDA and is associated with significantly fewer cases of necrotizing enterocolitis among infants with birth body weights <1250 g and significantly lower rates of elevated creatinine levels among neonates with birth body weights ranging from 1000 to 1500 g.